2021
DOI: 10.1007/s12325-021-01634-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Randomized Clinical Study of Netarsudil Ophthalmic Solution in Japanese Patients with Primary Open-Angle Glaucoma or Ocular Hypertension

Abstract: Introduction Netarsudil reduces intraocular pressure (IOP) by increasing aqueous outflow through the trabecular meshwork (TM) pathway and decreasing episcleral venous pressure. The primary objective of this phase 2 study was to evaluate ocular hypotensive efficacy and safety of three netarsudil concentrations (0.01%, 0.02%, and 0.04%) relative to its placebo over 4 weeks in Japanese patients with primary open-angle glaucoma (POAG) or ocular hypertension (OHT). Methods P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Zaman et al (2021),[ 9 ] in their study of 260 patients with OAG and ocular hypertension who were prescribed netarsudil 0.02% as monotherapy or added with concomitant therapy, reported a statistically significant reduction in IOP in both subgroups at 6 and 12 weeks. In a randomized study by Araie et al (2021)[ 10 ] on 207 patients, the IOP-lowering effect of three concentrations (0.01%, 0.02%, and 0.03%) of netarsudil ophthalmic solution was compared to placebo over 4 weeks in POAG and ocular hypertension patients. The study showed a superior mean reduction in diurnal IOP from baseline as compared to placebo ( P < 0.001) in all concentrations of netarsudil.…”
Section: Discussionmentioning
confidence: 99%
“…Zaman et al (2021),[ 9 ] in their study of 260 patients with OAG and ocular hypertension who were prescribed netarsudil 0.02% as monotherapy or added with concomitant therapy, reported a statistically significant reduction in IOP in both subgroups at 6 and 12 weeks. In a randomized study by Araie et al (2021)[ 10 ] on 207 patients, the IOP-lowering effect of three concentrations (0.01%, 0.02%, and 0.03%) of netarsudil ophthalmic solution was compared to placebo over 4 weeks in POAG and ocular hypertension patients. The study showed a superior mean reduction in diurnal IOP from baseline as compared to placebo ( P < 0.001) in all concentrations of netarsudil.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma is a leading cause of blindness affecting 64 million people in the world and is estimated to rise to 112 million by 2040 [ 1 , 2 ]. It affects about 4.65 million people in Japan alone [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glaucoma is a leading cause of blindness affecting 64 million people in the world and is estimated to rise to 112 million by 2040 [ 1 , 2 ]. It affects about 4.65 million people in Japan alone [ 1 ]. A major risk factor for disease progression is elevated intraocular pressure (IOP) [ 3 ], and every millimeter of IOP reduction is reported to significantly delay the disease progression, not only in patients with primary open-angle glaucoma (POAG) with elevated IOP but also in those with normal-tension glaucoma (NTG) [ 3 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations